"For nature, veredas and food": ethnobotany and ethno-ecology of Mauritia flexuosa L. and Mauritiella armata (Mart.) Burret in vereda communities of the northern sertão of Minas Gerais (PerCursos, 2024)
Mauritia flexuosa and Mauritiella armata are palm trees that define the Veredas in the north of Minas Gerais and are considered key species due to their ecological importance and socio-biocultural value for the traditional peoples, the veredeiros, who hold local ecological knowledge that permeates their relationship with the environment. However, their right to access to and use of the territory is limited by Protected Areas. Ethnobotanical and ethnoecological studies seek to understand how people interpret, classify and use the flora, creating productive alternatives and managing its use in a sustainable way. This study investigates the forms of use, management and conservation of key palms in three veredeiro communities in the Environmental Protection Area (EPA) of Rio Pandeiros, municipality of Bonito de Minas, in the north of Minas Gerais. Based on a qualitative analysis, semi-structured interviews were carried out, taking place after prior consent of interviewees and following health standards for the prevention of Covid-19. Data were transcribed, analyzed and organized in tables and illustrations. Eleven women and eight men were interviewed, who indicated the use of leaves, petioles, fruits and stems of palm trees. Fruits and leaves were more frequently cited, mainly in food and construction. In local forms of management, less harmful techniques are indicated, taking into account the palm trees and veredas. These communities have a close relationship with the environment and their knowledge can contribute to the participatory implementation of sustainable management strategies in the EPA of Rio Pandeiros. For this reason, their right of access and the sustainable use of biodiversity must be assured in their traditional territories.
Keywords: vereda communities; local ecological knowledge; ethnoconservation; Arecaceae